Realizing a Mobile Multimodal Platform for Serious Games Analytics - Laila Shoukry; Stefan Göbel (Serious Games Society, 2019)
This paper presents the design and development of "StoryPlay Multimodal", a mobile multimodal analytics platform for the evaluation of Serious Games. It is intended to serve researchers, teachers and educational game developers as a means to assess their Serious Game Design. This is done by capturing, pre-processing, synchronizing and visualizing multimodal serious games analytics and mobile sensor data from playtesting sessions. By linking log data with multimodal data, it is possible to uncover relations between design elements, gameplay interactions, context parameters and affective and cognitive states. This is crucial for gaining full insight into the session, even if not present with the player at the same location. After discussing design requirements, the architecture of the software, the different modules, additional features, implementation challenges and solutions are presented. The testing settings, participants and results are also discussed to demonstrate how the evaluation procedure can be applied to deliver valuable outcomes for Serious Games Research.